Analysis of the Values of Islamic Education in the Pilgrimage Tradition of the Tomb of Inyiak Kiramaik Among Indonesian Islamic Communities - Oktriyeni Ulfah; Fauzi Ananda; Faridatul Inayah (International Journal of Multidisciplinary Research of Higher Education, 2021)
One of the cultures of the Islamic community in Indonesia is to make pilgrimages to places that are considered sacred or also known as traditions. This study aims to analyze the values ​​of Islamic education in the traditions of the community at Inyiak Kiramaik grave. This study uses a qualitative method with a phenomenological approach. Sources of data were taken through in-depth interviews with ten informants consisting of two religious’ leaders, and eight people from the community who always make pilgrimages. The research data was taken by means of individual interviews to strengthen the interview data, the authors also made observations and analyzed using the Milles and Hubberman technique. The results showed three values ​​of Islamic education towards the Inyiak Kiramaik tomb, namely i) increasing faith; ii) preserving the tradition of visiting the tombs; iii) strengthening friendly relations between pilgrims. The results of this study can be used as initial data for future researchers to examine this issue in different contexts and issues.